THE INFLUENCE OF BIOACTIVE SUBSTANCES ISOLATED FROM PORCINE AORTA ON THE SERUM FATTY ACID COMPOSITION OF HYPERLIPIDEMIC RATS - Irina M. Chernukha; Liliya V. Fedulova; Elena A. Kotenkova (Теория и практика переработки мяса, 2018)
Based on results of fatty acid composition in serum of hyperlipidemic rats atherogenic index (AI) was calculated. The objects of the study were a commercial bioactive additive (BAA) containing a mixture of peptides isolated from the vessels of farm animals (Scientific and Production center of Revitalization and Health (SPRH), Russia), low molecular weight (LMUF), Mm<5kDa) and medium molecular weight (MMUF), Mm 5–30 kDa) ultrafiltrates of porcine aorta extract. Experimental hyperlipidemia was stimulated in male Wistar rats. After modeling animals in group 2 consumed 0.9 % sodium chloride solution, 3 groups — BAA, 4 groups — LMUF, 5 groups — MMUF, 1 group consisted of intact rats, contained under similar conditions. All studied samples were administered per os in a quantity of 0.3 mg protein / kg body weight for 14 days. As a result of the study, it was noted that in serum of rats treated with BAA there was polyunsaturated fatty acids (PUFA) increase by 67.2 % (P<0.05), while monounsaturated fatty acids (MUFA) was decreased by 29.5 % (P<0.05) compared to the control, but there was no change in AI. Per os administration of LMUF caused a similar effect as BAA: there was an increase in the proportion of PUFA by 2.5 times (p<0.05) compared with control, while MUFA decreased by 39.7 % (P<0.05), mainly due to a reduction of oleic acid by 66.3 % (P<0.05). The relative content of saturated fatty acids (SFA) decreased by 27.8 % (P<0.05), mainly due to reduction of palmitic acid content by 45.3 % (P<0.05) compared to the control, which contributed to a decrease in serum AI by 56.4 % (P<0.05). Per os administration of MMUF did not impact on relative content of MUFA, although the share of oleic acid was reduced by 48.0 % (P<0.05), there was also an increase of PUFA content by 85.8 % (P<0.05) compared with the control, serum AI reduced by 76.9 % (P<0.05) compared with the control group also due to a decrease of palmitic acid by 78.2 % (P<0.05).